Behavioral Inhibition and Fear: The Moderating Role of Emotional Competence and Gender in Preadolescents - Andrea Baroncelli; Stefania Righi; Carolina Facci; Enrica Ciucci (Children, 2025)
Background: The behavioral inhibition system (BIS) is a key motivational system that shapes human emotions and behaviors; specifically, the BIS regulates avoidance behaviors, and it is linked to negative emotions such as fear and anxiety. Previous studies have demonstrated a link between high BIS scores and attentional bias to threat in children, but literature is inconsistent. This may be due to differences in the individual awareness of emotions or in the accuracy of effectively detecting emotions. Moreover, the past literature has also found gender differences in BIS scores, which may suggest differential processes in boys and girls. Methods: The present study aims to investigate whether BIS scores were associated with an attentional facilitation index of fear in a sample of preadolescents (n = 264; 52.27% girls; M age = 12.98 years; SD = 0.89 years), considering the potential moderating role of (a) the awareness of others’ emotions as assessed by a self-report questionnaire, (b) emotion perception accuracy of fear as assessed by a laboratory task of emotion recognition, and (c) gender. Results: Our results showed that, only in males, higher scores of the BIS were associated with a lower attentional facilitation index of fear in the conditions of low levels of emotional competence (i.e., low levels of self-reported awareness of other emotions or low levels of accuracy recognition of fearful faces). Conclusions: Results were discussed in light of both theories of emotional development and practical clinical implications, with special attention to the emerged gender difference.